Spatial mapping and analysis of deforestation in Rompin, Pahang using remote sensing technique / Muhammad Amirul Shauqi Mohamad Rafi - Mohamad Rafi, Muhammad Amirul Shauqi (2023)
This study explores the spatial mapping and analysis of deforestation in Rompin, Pahang, utilizing remote sensing techniques. The main objectives are to produce a land cover classification, analyze changes specifically in the forest area for the years 2013, 2016, 2018, and 2020 using ArcMap, and create a change detection map. The methodology involves employing land classification and change detection techniques through the utihzation of ArcMap and Google Earth Engine. This research fulfils a requirement for the GSS 681 subject in the Bachelor's program of Surveying, Science, and Geomatics at the Faculty of Surveying, Science, and Geomatics. The findings of this study contribute to a better understanding of deforestation patterns in Rompin, Pahang, and provide valuable insights for land management and conservation efforts.